Numerical Simulation of Moisture Transfer Behaviors in Residential Walls in Hot and Humid Region - Jareemit, Daranee (Journal of Architectural/Planning Research and Studies (JARS), 2018)
This paper evaluates moisture transfer behaviors and its accumulation in eighteen wall assemblies of Thai detached houses via using 2D numerical hygrothermal simulation software. It is found that moisture accumulation in wall assemblies is caused by capillary actions of ground water and outdoor weather condition. The moisture accumulation within the walls varies depending on the wall height. The moisture accumulation below 12.5 centimeters wall height is affected by ground water and its effect gradually reduces with distance from the ground. The moisture accumulation in external wall is influenced by outdoor weather condition, which results in large moisture distribution in external plastering material. The wall systems with two side of grade beam attached the soil potentially have the highest moisture content. Autoclaved aerated concrete-block wall tends to have higher moisture accumulation than those of the masonry and concrete-block walls. These investigations can give Architects and engineers understanding how moisture behaves in residential walls in hot and humid climates. They could properly select the wall materials as well as construction systems to avoid moisture problems in their home.